Association of brain morphology and phenotypic profile in patients with unruptured intracranial aneurysm - Li, Jianyu; Tan, Zeming; Yi, Xiaoping; Fu, Yan; Zhu, Liping; Zeng, Feiyue; Han, Zaide; Ren, Zhanbing; Zhang, Yuanchao; Chen, Bihong T. (Frontiers in Aging Neuroscience, 2023)
Introduction Studies have found a varying degree of cognitive, psychosocial, and functional impairments in patients with unruptured intracranial aneurysms (UIAs), whereas the neural correlates underlying these impairments remain unknown. Methods To examine the brain morphological alterations and white matter lesions in patients with UIA, we performed a range of structural analyses to examine the brain morphological alterations in patients with UIA compared with healthy controls (HCs). Twenty-one patients with UIA and 23 HCs were prospectively enrolled into this study. Study assessment consisted of a brain magnetic resonance imaging (MRI) scan with high-resolution T1-weighted and T2-weighted imaging data, a Montreal Cognitive Assessment (MoCA), and laboratory tests including blood inflammatory markers and serum lipids. Brain MRI data were processed for cortical thickness, local gyrification index (LGI), volume and shape of subcortical nuclei, and white matter lesions. Results Compared to the HCs, patients with UIA showed no significant differences in cortical thickness but decreased LGI values in the right posterior cingulate cortex, retrosplenial cortex, cuneus, and lingual gyrus. In addition, decreased LGI values correlated with decreased MoCA score (r = 0.498, p = 0.021) and increased white matter lesion scores (r = −0.497, p = 0.022). The LGI values were correlated with laboratory values such as inflammatory markers and serum lipids. Patients with UIA also showed significant regional atrophy in bilateral thalami as compared to the HCs. Moreover, the LGI values were significantly correlated with thalamic volume in the HCs (r = 0.4728, p = 0.0227) but not in the patients with UIA (r = 0.11, p = 0.6350). Discussion The decreased cortical gyrification, increased white matter lesions, and regional thalamic atrophy in patients with UIA might be potential neural correlates of cognitive changes in UIA.